Intraoperative haemorrhagic choroidal detachment during MicroIncision Vitrectomy Surgery (MIVS): a unique mechanism. Issue 2 (25th February 2022) - Markan, Ashish; Ayyadurai, Nikitha; Singh, Simar Rajan; Katoch, Deeksha
Abstract : Haemorrhagic choroidal detachment (HCD) is a dreaded intraoperative complication of ophthalmic surgery, despite being rare. Multiple systemic and ocular risk factors of HCD have been reported. Acute hypotony during surgery is considered one of the most important precipitating factors. We herein describe a series of events during pars plana vitrectomy surgery for management of rhegmatogeneous retinal detachment which lead to localised HCD. We believe that the pathogenesis of localised HCD is related to compressive decompressive forces during the final tie of the encircling element after fluid air exchange.